Hubungan Penggunaan Alat Pelindung Diri (APD) Dengan Kadar Hemoglobin Pada Pekerja Wanita Yang Terpapar Bahan Bakar Di SPBU Kota Kendari - Lade Albar Kalza (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
Occupational health is an important aspect in maintaining worker productivity and safety, particularly in sectors with a high risk of chemical exposure such as gas stations (SPBU). Gas station workers are potentially exposed to hazardous chemical compounds such as benzene, toluene, and xylene which may affect the hematopoietic system and lead to decreased hemoglobin (Hb) levels. The use of Personal Protective Equipment (PPE) is one of the preventive measures to minimize exposure to these hazardous substances. This study aimed to determine the relationship between the use of Personal Protective Equipment (PPE) and hemoglobin levels among female workers exposed to fuel at gas stations in Kendari City. This study employed a quantitative research design with a descriptive analytic approach using a cross-sectional method. The population in this study consisted of all female fuel filling operators working at gas stations in Kendari City, totaling 30 workers, who were all included as research samples. Data on PPE usage were obtained through observation and questionnaires, while hemoglobin levels were measured using a Hematology Analyzer with venous blood samples collected in EDTA tubes. Data analysis was conducted using univariate and bivariate statistical tests to determine the relationship between PPE usage and hemoglobin levels. The results showed that out of 30 respondents, 21 (70%) had normal hemoglobin levels and 9 (30%) had abnormal hemoglobin levels. A total of 20 respondents (66.7%) used PPE according to the required standards, while 10 respondents (33.3%) did not meet the PPE requirements. Statistical analysis showed a p-value of 0.104 (p > 0.05), indicating that there was no significant relationship between PPE usage and hemoglobin levels among female gas station workers in Kendari City. The study concludes that the use of PPE does not have a significant relationship with hemoglobin levels among female gas station workers in Kendari City. However, the consistent use of PPE is still recommended as a preventive measure to protect workers from exposure to hazardous chemicals in the workplace.